The influence of artificial salivary pH on nickel ion release and the surface morphology of stainless steel bracket-nickel-titanium archwire combinations - Ida Bagus Narmada; Natalya Tantri Sudarno; Achmad Sjafei; Yuli Setiyorini (Dental Journal (Majalah Kedokteran Gigi), 2017)
Background: In the oral cavity, orthodontic appliances come into contact with saliva which may cause corrosion capable of changing their surface morphology due to the release of metal ions. Surface roughness can influence the effectiveness of tooth movement. One of the ions possibly released when body fluid comes into contact with brackets and archwire is nickel ion (Ni). Ni, one of the most popular components of orthodontic appliances, is, however, a toxic element that could potentially increase the likelihood of health problems such as allergic responses during treatment. Purpose: The purpose of this study was to investigate the effect of different artificial salivary pH on the ions released and the surface morphology of stainless steel (SS) brackets-nickel-titanium (NiTi) and archwire combinations. Methods: Brackets and archwires were analyzed by an Energy Dispersive X-Ray Detector System (EDX) to determine their composition, while NiTi archwire compound was examined by means of X-ray Diffraction (XRD). The immersion test was performed at artificial salivary pH levels of 4.2; 6.5; and 7.6 at 37°C for 28 days. Ni ion release measurement was performed using an Atomic Absorption Spectroscopy (AAS). Surface morphology was analyzed by means of a Scanning Electron Microscopy (SEM). Results: The chemical composition of all orthodontic appliances contained Ni element. In addition, XRD was depicted phases not only NiTi but also Ni, Titanium, Silicon and Zinc Oleate. The immersion test showed that the highest release of Ni ions occured at a pH of 4.2, with no significant difference at various levels of pH (p=.092). There were surface morphology changes in the orthodontic appliances. It was revealed that at a pH of 4.2, the surfaces of orthodontic appliances become unhomogenous and rough compared to those at other pH concentrations. Conclusion: The reduction of pH in the artificial saliva increases the amount of released Ni ions, as well as causing changes to the surface morphology of brackets and archwires.